(untitled) (Journal of Management and Business Education, 2019)
The objective of this work is to present a quantitative methodology used for the evaluation of the transversal competence Teamwork and Leadership in the course Human Resources Management, Degree in Management and Public Administration, Universitat Politècnica de València. Lecturers have collected data from peer evaluation and self-assessment of students. With this, we have made a quantitative evaluation through the application of an adequacy coefficient that has allowed to verify which students adjusted better to the level required by the lecturers in the different items that build the transversal skill, both from the point of view of the companions and oneself. In addition, it has been proven in which way teamwork has reinforced the individual work of each student. The evaluation method presented in this article is of universal use, since it can be adapted to any other course of any other title, or educational level, even undergraduate. The knowledge of the results allows to better guide the teaching performance to the learning results of the students through teamwork.